Two yeast genes with similarity to TCP-1 are required for microtubule and actin function in vivo. - Chen, X (1994)
We have isolated cold-sensitive mutations in two genes of the yeast Saccharomyces cerevisiae, BIN2 and BIN3, that cause aberrant chromosome segregation in vivo. BIN2 and BIN3 encode essential proteins that are similar to each other and to TCP-1. TCP-1 and TCP-1-like proteins are components of the eukaryotic cytoplasmic chaperonin that facilitates folding of tubulins and actin in vitro. Mutations in BIN2 and BIN3 cause defects in microtubule and actin assembly in vivo and confer supersensitivity to the microtubule-destabilizing drug benomyl. Overexpression of TCP1, BIN2, BIN3, or ANC2, a fourth member of the TCP-1 family in yeast, does not complement mutations in the other genes, indicating that the proteins have distinct functions. However, all double-mutant combinations are inviable; this synthetic lethality suggests that the proteins act in a common process. These results indicate that Bin2p and Bin3p are components of a yeast cytoplasmic chaperonin complex that is required for assembly of microtubules and actin in vivo.